Mental health and risk behaviors among secondary school students: A study on ethnic minorities - Yong Kang Cheah; Chee Cheong Kee; Kuang Hock Lim; Mohd Azahadi Omar (Elsevier, 2021)
Background: Mental health disorders are highly correlated with risk behaviors. The objective of the present study is to examine the relationship between risk behaviors and mental health among school-going students with a focus on ethnic minorities. Methods: The National Health and Morbidity Survey (NHMS) 2017 (n = 8230) was used for analyses. It was a nationwide survey conducted in Malaysia. The dependent variables were measured by three risk behaviors (cigarette smoking, alcohol drinking and use of illicit drugs). Probit regressions were utilized to examine the effect of mental health on the probability of smoking, drinking and using illicit drugs. Demographic and lifestyle factors were used as the control variables. Truancy was identified as a mediating variable. Results: Anxiety, depression and suicidal ideation affected cigarette smoking, alcohol drinking and use of illicit drugs through mediation of truancy. After controlling for demographic and lifestyle factors, students with anxiety, depression and suicidal ideation were more likely to smoke, drink and use illicit drugs compared with their peers without any mental health disorders. Furthermore, the likelihood of consuming cigarettes, alcohol and illicit drugs was found to be higher among students who played truant than those who did not. Conclusion: Mental health plays an important role in determining participation in risk behaviors among ethnic minority students in Malaysia. Public health administrators and schools have to be aware that students who suffer from mental health disorders are likely to indulge in risk behaviors.